2013
DOI: 10.5846/stxb201203210387
|View full text |Cite
|
Sign up to set email alerts
|

The spatial distribution pattern of overwintering egg ofMonolepta hieroglyphica(Motschulsky) in corn field

Abstract: The objectives of this work were to clarify the spatial distribution pattern of the overwintering eggs of M. hieroglyphica ( Motschulsky) . An investigation with stratified random sampling was conducted on the egg number in corn field of Jinzhong, Shanxi province in October 2011. The spatial distribution pattern of the overwintering eggs of M. hieroglyphica in soil was studied by determination of frequency distribution, aggregated indices, the improved Iwao忆 s regression equation and Taylor忆s power law. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Leaf beetle Monolepta hieroglyphica (Motschulsky, 1858) is among the most destructive pest insects of cereals and vegetables in China (Li et al, 2014; Liu et al, 2016a, 2016b; Zhang, 2012; Zhang Cong et al, 2013; Zhang et al, 2014a). In the present study, we identified one GGPPS by transcriptome sequencing and molecular cloning and designated as MhieGGPPS.…”
Section: Introductionmentioning
confidence: 99%
“…Leaf beetle Monolepta hieroglyphica (Motschulsky, 1858) is among the most destructive pest insects of cereals and vegetables in China (Li et al, 2014; Liu et al, 2016a, 2016b; Zhang, 2012; Zhang Cong et al, 2013; Zhang et al, 2014a). In the present study, we identified one GGPPS by transcriptome sequencing and molecular cloning and designated as MhieGGPPS.…”
Section: Introductionmentioning
confidence: 99%